(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article deals with the knowledge questions of the doctrine of the great ancestor Ahmet Yassawi. In difference from writers and philosophers Ahmet Yassawi has soiled special attention to internal knowledge (Maghrifat). For achievement of internal knowledge according to Yassawi’s doctrine it is necessary to pay attention to heart purity. Because heart, is the binding bridge of this and other world. It is possible to pass on this bridge by spiritual clarification of the person, clarification from heart dirt, enlightenment, mystical eminences, i.e. on Sufism by Sayr Suluk. In the course of disclosure of heart, people got to some states and even cases which are considered in Yasaui’s doctrines. They in turn are explained by the following terms:Kashf, Mushakhada,Vuslat, Fana and Baqa, Uazhd, Istighraq, Sakr, etc. According to Yassawi’s doctrine a main goal of internal knowledge is God knowledge, to meet him and to be with him uniform. According to Yassawi’s doctrine this level among knowledge is the greatest and real happiness. Key words: Ahmet Yassawi, Maghrifat, Khal, Sayr Suluk, Fana, Baqa, Sakhr, Makhu, Kashf, Mushakhada.